The three little wolves and the big bad pig - Trivizas, Eugenios; Oxenbury, Helen (New York : Margaret K. McElderry Books, 1993)
An altered retelling of the traditional tale about the conflict between pig and wolf--with a surprise ending.
Elem. School Library Collection
School Library Journal starred
Wilson's Children
5.1
K-3
K-3
Keywords: Animals -- Folklore; Folklore; Animals -- Folklore; Folklore